IBM ILOG CP optimizer for scheduling: 20+ years of scheduling with constraints at IBM/ILOG - Laborie, Philippe; Rogerie, Jérôme; Shaw, Paul; Vilím, Petr (Constraints : an international journal, 2018)
IBM ILOG CP Optimizer is a generic CP-based system to model and solve scheduling problems. It provides an algebraic language with simple mathematical concepts to capture the temporal dimension of scheduling problems in a combinatorial optimization framework. CP Optimizer implements a model-and-run paradigm that vastly reduces the burden on the user to understand CP or scheduling algorithms: modeling is by far the most important. The automatic search provides good performance out of the box and it is continuously improving. This article gives a detailed overview of CP Optimizer for scheduling: typical applications, modeling concepts, examples, automatic search, tools and performance.